Comparación del desarrollo psicomotor, en niños de 4 a 5 años entre una escuela urbana y otra suburbana - Tacuri Romero, Julia Nathaly (2015)
In this research a comparative, quantitative, qualitative study on psychomotor development was conducted in two schools: one of Urban Sector and other Suburban Sector, whose results led to know if there is psychomotor retardation and determine what area children are more involvement. For this, a sample of 27 children of an urban school Education Unit "The Immaculate" and 27 children of a suburban school, "Dorotea Carrion" city of Loja was taken during the period 2014 to 4-5 years old. To assess psychomotor development Denver test was used, the assessment includes four areas of Psychomotor Development: Motor, Fine Motor, Language and Personal - Social. In making the assessment, increased psychomotor retardation in the suburban school with a percentage of 25.92% compared to urban school children in the 22.22% was found. The area most affected in school “Dorotea Carrion” was Fine Motor at 18.51%. Key words: Psychomotor Development, Denver Test.